TRANSFORMATION OF FUNCTIONS OF FAMILY MEMBERS IN POSTMODERN SOCIETY - Davronova Oysulton Davronkulovna (Journals Park Publishing, 2022)
This article talks about the transformation of functions of family members in postmodern society. The family tests the customs of the people, society and life. He keeps the good ones in his bosom and passes them on to future generations. The family educates its children and instills them with universal values, giving them the initial social orientation. By integrating their children into the larger flow of society, the Family also influences the direction, economy, culture and education of society.
Keywords: postmodern society, family members, function